Random binomial tree models and put options - Ganikhodjaev, Nasir; Bayram, Kamola (IIUM, 2012)
In this paper we introduce and study the simplest random binomial tree model. Usual binomial tree model is prescribed by pair of numbers (u, d), where u denotes the increase rate of the stock over the fixed period of time and d denotes the decrease rate, with 0< d < 1< u. We call the pair (u, d) an environment of the binomial tree model. A pair (Un, Dn), where Un and Dn are the sequences of independent, identically distributed random variables with 0< Dn < 1< Un for all n, is called a random environment and binomial tree model with random environment is called random binomial tree model. In this paper we define and study European put option for such models.